If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-4w + 8) + -6w = 2(w + -6) + -8 Reorder the terms: -4(8 + -4w) + -6w = 2(w + -6) + -8 (8 * -4 + -4w * -4) + -6w = 2(w + -6) + -8 (-32 + 16w) + -6w = 2(w + -6) + -8 Combine like terms: 16w + -6w = 10w -32 + 10w = 2(w + -6) + -8 Reorder the terms: -32 + 10w = 2(-6 + w) + -8 -32 + 10w = (-6 * 2 + w * 2) + -8 -32 + 10w = (-12 + 2w) + -8 Reorder the terms: -32 + 10w = -12 + -8 + 2w Combine like terms: -12 + -8 = -20 -32 + 10w = -20 + 2w Solving -32 + 10w = -20 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. -32 + 10w + -2w = -20 + 2w + -2w Combine like terms: 10w + -2w = 8w -32 + 8w = -20 + 2w + -2w Combine like terms: 2w + -2w = 0 -32 + 8w = -20 + 0 -32 + 8w = -20 Add '32' to each side of the equation. -32 + 32 + 8w = -20 + 32 Combine like terms: -32 + 32 = 0 0 + 8w = -20 + 32 8w = -20 + 32 Combine like terms: -20 + 32 = 12 8w = 12 Divide each side by '8'. w = 1.5 Simplifying w = 1.5
| 4y+8=6y | | 5.5r+r=90 | | log(x-1)+log(x-2)=1 | | z+1=1halfz+4 | | X+(x-3)9=3 | | 3log[5](12x)=18 | | 3-(-2(5))= | | 20=x-7 | | 0+50*1-60*0+10=0 | | -61/2x=0 | | -7(5x+3)=154 | | 8y+3z=21 | | -1/16=x-11/12 | | 4y+12=4 | | 6r-5=8r+9 | | 5x^3+21x^2+3x=0 | | -5x+9=10 | | 8r=-136 | | 12-7x=23 | | 2x(3+4)=552 | | 20x+15y=105 | | 6x-7=6x+7x | | -8+14b+15b^2=0 | | -5x+7=3-6x | | 3x+24=-3(x-6) | | X-1(-1)+X=10 | | 4x^3+8x^2-5n-10=0 | | 9c-6+c= | | 10x-(3-x)=31 | | 8y+8=z | | 4b^2-5b-5=0 | | -8(x+9)=8x-40 |